Formulasi dan Uji Mutu Fisik Sabun Herbal Padat Ekstrak Kulit Batang Kayu Manis (Cinnamomum burmanni): Formulation and Physical Quality Test of Solid Herbal Soap Cinnamon (Cinnamomum burmanni) Bark Extract - Dewinta Hesti Dwi Nurani; Elly Purwati; Cikra Ikhda Nur Hamidah Safitri (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Researchers have conducted research on the 1% 3% concentration of cinnamon bark extract (Cinnamomum burmanii.) For the manufacture of herbal solid soap preparations and tested the physical quality of herbal solid soap preparations. Cinnamon has antibacterial properties. This study aims to determine the extract of cinnamon bark (Cinnamomum burmanii.) Can be used as solid soap with a concentration of 1%, 3% which meets the requirements of the physical quality test which includes pH test, foam power test, organoleptic test, and homogeneity test. The design of this research is experimental research and the data were analyzed descriptively. Cinnamon bark extract was obtained from the maceration process with 70% ethanol. Making herbal solid soap formulations and soap making using the Cold Process method. The treatment in this study the concentration method added was 1% 3%. The homogeneity test showed that the three solid soap formulations of cinnamon bark extract (Cinnamomum burmanii) remained homogeneous as indicated by the absence of coarse grains or particles on the surface of the herbal solid soap for cinnamon bark extract (Cinnamomum burmanii.) High stability of the foam with a height of 9cm and a pH value. already in accordance with SNI 06 - 3532 - 2016 with a pH value of 9-11 the organoleptic test shows different results.